PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PADA TOKO RITEL MAMI KEPOO BUMDES NGABEI SEJAHTERA) - Wawan Nurdiansyah; Mardiana Nisa B; Iis Ismiati (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study aims to determine the effect of price and product quality on purchasing decisions at Mami Kepoo Bumdes Ngabei Sejahtera Retail stores. The method used in this study is using quantitative methods. Determination of the sample using the Lemeshow Technique and the sample number of 100 respondents. Data collection techniques use observation, interviews, literature studies and questionnaires. While the data analysis techniques used are validity tests, reliability tests, classical assumption tests, multiple linear regression tests, and hypothesis tests. Based on the results of the study, it shows that the price partially has no significant effect on the purchase decision as evidenced by the calculated t value of the price of -1.313 < t table 1.984 with a significant value of 0.192 > 0.05. While product quality partially has a significant effect on purchasing decisions as evidenced by a calculated t value of 5.90 0 > t table 1.984with a significance value of 0.000 < 0.05. Meanwhile, simultaneously price and product quality have a positive and significant effect on purchasing decisions with a calculated f value of 17.414 < f table 3.090 significant value of 0.000 < 0.05.